New and rare deep-sea majoid crabs (Crustacea: Brachyura) from Papua New Guinea - Ng, Peter K. L.; Forges, Bertrand Richer De; Lee, Bee Yan (Zootaxa, 2023)
Additional spider crab (superfamily Majoidea) material from four major French-led expeditions to the Papua New Guinea region were examined in this study. One new genus and four new species from the families Inachidae and Oregoniidae are described. Dorhynchus profundus n. sp. is close to D. rostratus (Sakai, 1932) but can easily be separated by the shape of the ambulatory dactylus and the proportionately lower protogastric spines. Achaeus pholcus n. sp. is unusual in that it occurs in deeper waters (beyond 500 m), and can be separated from A. lacertosus Stimpson, 1857, A. villosus Rathbun, 1916, and A. brevidactylus Sakai, 1938, by its distinctive carapace shape, structure of the frontal margin, regions of the carapace, antennular fossa, ambulatory dactylus, male pleon, and proportions of the chela. Parapleisticantha aie n. sp. is closest to P. japonica Yokoya, 1933, but differs in its proportionately longer carapace, more elongated basal antennal article, longer third maxilliped ischium and the relatively less curved male first gonopod with the distal part differently structured. A new genus (Orbicantha n. gen.) with one new species (Orbicantha sacrebleu n. gen., n. sp.) is also described; it is allied to Pleistacantha Miers, 1879, Parapleisticantha Yokoya 1933, and Pleisticanthoides Yokoya, 1933, but is distinctive in its subcircular carapace, shorter regions, short pseudorostral spines, possession of spines on the gastric, cardiac and branchial regions, some of which have rounded tips, a short ocular peduncle, a very short third antennal article, a quadrate epistome, and the more reduced P4 and P5. New records from the family Epialtidae are also reported: Griffinia gilloloensis (Rathbun, 1916), Hyastenus borradailei (Rathbun, 1907), and Oxypleurodon luzonicum (Rathbun, 1916). The taxonomy of Grypachaeus tenuicollis Takeda, 1978 (Oregoniidae) and Griffinia lappacea (Rathbun, 1918) (Epialtidae) is also discussed.